A Threatening Intellectual Environment: Why Females Are Susceptible to Experiencing Problem-Solving Deficits in the Presence of Males - Inzlicht, Michael; Ben-Zeev, Talia (Psychological Science, 2000)
Does placing females in environments in which they have contact with males cause deficits in their problem-solving performance? Is a situational cue, such as gender composition, sufficient for creating a threatening intellectual environment for females—an environment that elicits performance-impinging stereotypes? Two studies explored these questions. Participants completed a difficult math or verbal test in 3-person groups, each of which included 2 additional people of the same sex as the participant (same-sex condition) or of the opposite sex (minority condition). Female participants in the minority condition experienced performance deficits in the math test only, whereas males performed equally well on the math test in the two conditions. Further investigation showed that females' deficits were proportional to the number of males in their group. Even females who were placed in a mixed-sex majority condition (2 females and 1 male) experienced moderate but significant deficits. Findings are discussed in relation to theories of distinctiveness, stereotype threat, and tokenism.